A Cluster Randomized Trial of Tai Chi vs Health Education in Subsidized Housing: The MI‐WiSH Study. Issue 9 (22nd May 2019) - Lipsitz, Lewis A.; Macklin, Eric A.; Travison, Thomas G.; Manor, Brad; Gagnon, Peggy; Tsai, Timothy; Aizpurúa, Ilean Isaza; Lo, On‐Yee; Wayne, Peter M.
Abstract : OBJECTIVES: Tai Chi (TC) may benefit older adults with a variety of diseases and disabilities. We tested the hypothesis that TC improves physical function in older adults living in low‐income housing facilities. DESIGN: Cluster randomized controlled trial. SETTING: Subsidized housing facilities in Boston, Massachusetts, and neighboring communities. PARTICIPANTS: Volunteers were recruited from 15 facilities. The 180 randomized participants were 60 years of age or older, able to understand English and participate in TC, expected to remain in the facility for 1 year, and able to walk independently. INTERVENTION: TC classes were conducted in the housing facilities twice/week for 1 year and compared with monthly health promotion educational classes and social calls. MEASUREMENTS: The primary outcome was physical function measured by the Short Physical Performance Battery (SPPB). Secondary outcomes included other aspects of physical and cognitive function, and falls. RESULTS: An interim analysis revealed less improvement over 12 months in SPPB scores among TC participants (+.20 units; 95% confidence interval [CI] = −.20 to +.60; P = .69) vs control participants (+.51 units; 95% CI = +.15 to +.87; P = .007), a difference of −.31 units (95% CI = −.66 to .04; P = .082). This met the criterion for futility, and the Data Safety Monitoring Board recommended trial termination. No differences were found in 6‐ or 12‐month changes favoring TC in any secondary outcomes or adverse events. CONCLUSION: In older adults with multiple chronic conditions living in subsidized housing facilities, 6 and 12 months of twice/week TC classes were not associated with improvements in functional health. J Am Geriatr Soc 67:1812–1819, 2019